2015
DOI: 10.1017/jfm.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

On the role of adaptivity for robust laminar flow control

Abstract: In boundary-layer flows, one may reduce skin-friction drag by delaying the onset of laminar-to-turbulent transition via the attenuation of small-amplitude Tollmien-Schlichting (TS) waves. In this work, we use numerical simulations and experiments to compare the robustness of adaptive and model-based techniques for reducing the growth of two-dimensional TS disturbances. In numerical simulations, the optimal linear quadratic Gaussian (LQG) regulator shows the best performance under the conditions it was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…This paper focussed on optimal control and no other model uncertainties, such as input/actuator uncertainties and uncertainties in the Reynolds number were addressed. Recently in Fabbiane et al (2015) it is shown through experiments that deviations from the design conditions can destabilise optimal controllers. Future work will also focus on addressing model uncertainties by integrating this method in a H ∞ robust control framework.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper focussed on optimal control and no other model uncertainties, such as input/actuator uncertainties and uncertainties in the Reynolds number were addressed. Recently in Fabbiane et al (2015) it is shown through experiments that deviations from the design conditions can destabilise optimal controllers. Future work will also focus on addressing model uncertainties by integrating this method in a H ∞ robust control framework.…”
Section: Resultsmentioning
confidence: 99%
“…This led to the use of reduced order modelling techniques for control design that make no assumptions on the flow geometry and the shape and distribution of the actuators/sensors. This approach, also known as the reduced order modelling approach, accounts for physically realisable localised actuators/sensors and has been validated in experiments (Samimy et al 2007;Pastoor et al 2008;Fabbiane et al 2015). Galerkin projection is commonly applied, in which a reduced order model (ROM) is obtained by projecting the Navier-Stokes equations onto a reduced set of modes.…”
Section: Model Reduction and Localised Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach to the robustness problem is given by adaptive control strategies 42,43 , such as the FXLMS algorithm. Rather than determining a fixed control law, a proper actuator response is identified from sensor input, based on an approximate model for the flow behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For applications in boundary layer transition control, the reader is referred to the works of Fabbiane et al [16,18], and the work of Bagheri et al [2] which presents a nice introduction to optimal control for applications in fluid mechanics. The success of LQG controllers is related to their optimality, the design being made in two steps, from the solution of two Riccati equations for the estimation and control problems, which guarantee stability, as long as the system is observable and controllable.…”
Section: Lqg Controlmentioning
confidence: 99%